RANGE OF MOTION (ROM) EXERCISES IN POST-OPERATIONAL PATIENT POST OPEN REDUCTION INTERNAL FIXATION (ORIF) MANAGEMENT - Latifah, Siti (Universitas Aisyah Pringsewu, 2023)
The medical action that can be taken in dealing with fracture conditions is to perform an Open Reduction Internal Fixation (ORIF) procedure. When the bone fragments have been reduced, and the fixation device has been installed, it will cause severe pain. Non-pharmacological pain management can be done in ORIF postoperative patients by doing Range of Motion (ROM) exercises. This research was conducted at Koja Hospital in May - June 2023. The aim of this study was to determine the effectiveness of ROM on pain intensity in post-ORIF Extremity patients immediately, carried out on the 2nd day after surgery, 4 times in 2 consecutive days. Each movement is repeated 8 times with 30 minutes of practice time. The research method uses quantitative research with Quasi-experimental pre-a post-tests without control. The number of samples was 18 postoperative ORIF extremity patient respondents who were measured by Numeric Rating Scale (NRS) pain before and after ROM exercises. The results showed that there was an effect of ROM training on the pain intensity of postoperative ORIF patients using the Paired T-Test with a p-value of 0.000 ? 0.05, and it was found that there was a decrease in the average pain scale from before ROM 5.50 to a pain scale of 3.83 after ROM training. The conclusion is that ROM exercises are effective in reducing pain in postoperative ORIF Extremity patients at Koja Hospital. Keywords: Fracture, Postoperative pain intensity, Range of Motion